2001
DOI: 10.2337/diacare.24.8.1397
|View full text |Cite
|
Sign up to set email alerts
|

Postchallenge Hyperglycemia and Mortality in a National Sample of U.S. Adults

Abstract: OBJECTIVE—Although postchallenge hyperglycemia is a well-established feature of type 2 diabetes, its association with risk of mortality is uncertain. Therefore, the aim of this study was to assess the independent association of fasting and 2-h glucose levels with all-cause and cardiovascular disease (CVD) mortality. RESEARCH DESIGN AND METHODS—We analyzed data from the Second National Health and Nutrition Examination Survey (NHANES II) Mortality Study, a prospective cohort study of U.S. adults e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
134
1
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(142 citation statements)
references
References 30 publications
2
134
1
5
Order By: Relevance
“…Diabetes is associated with increased mortality, especially from CVD [5,6]. Hyperglycaemia, in the absence of clinically diagnosed diabetes, is also associated with an increased CVD risk [7,8,9,10,11,12,13,14]. Several studies indicated a greater relative risk of CVD with diabetes [4,14] and hyperglycaemia [7,11,15] among women than men, while the Hoorn Study reported no consistent differences [9].…”
mentioning
confidence: 99%
“…Diabetes is associated with increased mortality, especially from CVD [5,6]. Hyperglycaemia, in the absence of clinically diagnosed diabetes, is also associated with an increased CVD risk [7,8,9,10,11,12,13,14]. Several studies indicated a greater relative risk of CVD with diabetes [4,14] and hyperglycaemia [7,11,15] among women than men, while the Hoorn Study reported no consistent differences [9].…”
mentioning
confidence: 99%
“…Recent studies indicated that fasting glucose concentrations alone do not identify individuals at increased risk of death associated with hyperglycemia and that mealtime glycemia significantly contributes to overall glycemic control and coronary artery disease mortality [9][10][11]. In this regard, even subjects with impaired glucose tolerance are also at risk of death similar to type 2 diabetes patients.…”
Section: Discussionmentioning
confidence: 99%
“…Postprandial hyperglycemia observed in impaired glucose tolerance may be a prospective determinant of cardiovascular disease [9][10][11] and the efficacy of intervention to treat this abnormality has been reported or is currently under investigation [12,13]. The above background suggests that we have to treat patients with early type 2 diabetes more intensively and to continue to search for effective and acceptable oral hyperglycemic agents for early type 2 diabetes.…”
mentioning
confidence: 99%
“…At the end of the treatment period, rats in each group were starved overnight but had access to water ad libitum, weighed and sacrificed by cervical dislocation while under anesthesia, 2 ml blood was collected from each rat by cardiac puncture into plain tube [7,8]. The blood was allowed to stand for 5 minutes and then centrifuged at 3500 rpm (Beckman GS-6R, Germany) for 10 minutes at 4°C.…”
Section: Serum and Tissue Preparationmentioning
confidence: 99%